Analisis Pengaruh Jumlah Produksi, Kurs, Harga Jual, dan Tingkat Suku Bunga terhadap Ekspor Batubara Indonesia ke Hong Kong Tahun 1994–2023 (Lembaga Pengembangan Kinerja Dosen, 2026)
International trade is one of the main drivers of economic growth, especially for countries with natural resource advantages like Indonesia. Coal is one of the flagship export commodities in the mining sector, contributing significantly to the country's foreign exchange. Although Indonesia is one of the largest coal producers and exporters in the world, the performance of coal exports to Hong Kong shows a fluctuating trend and is relatively lower compared to other major destination countries. This condition is influenced by various economic factors, both in terms of supply and macroeconomic factors, making a more specific empirical study on the destination country necessary. This study aims to analyze the effect of production volume, exchange rates, selling prices, and interest rates on Indonesia's coal exports to Hong Kong during the period 1994–2023. This study uses secondary time series data and is analyzed using multiple linear regression methods. The analysis results indicate that simultaneously, production volume, exchange rate, selling price, and interest rate significantly affect Indonesia's coal exports to Hong Kong. Partially, production volume, exchange rate, and selling price have a positive and significant effect on coal exports, while the interest rate has a negative and significant effect. These findings suggest that increasing production capacity, a weakening exchange rate, and rising selling prices can boost coal exports, whereas rising interest rates tend to suppress export performance through higher financing costs. The implications of this study emphasize the importance of macroeconomic policy stability and sustainable management of the mining sector to maintain the competitiveness of Indonesian coal exports, especially to countries with dynamic demand characteristics like Hong Kong.